THE EFFECT OF SERVICE FEATURES ON LOYALTY IN MEDIATION OF BNI TAPLUS UGM CUSTOMER SATISFACTION - Benny Umbara; Haddy Suprapto; Titik Kusmantini (Jurusan Teknik Informatika, 2021)
The increasing number of banking companies are switching to work on the consumer market, resulting in higher competition between banks. This research was conducted to analyze and determine the effect of BNI Taplus service features on customer satisfaction and customer loyalty and the effect of BNI Taplus service features on customer loyalty mediated by customer satisfaction. The data were obtained by distributing surveys to several respondents. The sample consisted of 100 respondents. This research analysis test using path analysis with the SEM method. The results of this research analysis test found several things that service features did not have a significant effect on customer satisfaction and loyalty of BNI Taplus UGM Yogyakarta Branch. While customer satisfaction is able to mediate positively and significantly the effect of service features on customer loyalty at BNI Taplus UGM Yogyakarta Branch.